The Influence of Service Quality and Customer Satisfaction on Customer Loyalty at the Brastagi Gatot Subroto Supermarket Medan - Hetti Elviani; Julianto Hutasuhut (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The purpose of this study is to examine how customer happiness and service quality affect customer loyalty at Brastagi Gatot Subroto Supermarket in Medan. This study used a quantitative methodology. Observation, recordkeeping, and questionnaires are all used as research data collection methods. The Supermarket Brastagi Gatot Subroto Medan's entire customer base makes up the research population. 150 clients of the Brastagi Gatot Subroto Supermarket in Medan served as samples for this study, which was calculated using the Hair formula. Multiple linear regression analysis utilizing the SPSS Version 25.00 application is the data analysis method. The study's findings demonstrate that customer loyalty at the Supermarket Brastagi Gatot Subroto Medan is positively and significantly influenced by service quality, with a coefficient value of 0.603, a t-count > t-table value of (10.769 > 1.6550), and a significant value of 0.000 less than 0.05. At the Supermarket Brastagi Gatot Subroto Medan, customer satisfaction has a positive and substantial impact on customer loyalty, with a coefficient value of 0.319, t-count > t-table (5.718 > 1.6550), and a significant 0.000 less than 0.05. With a value of Fcount (145.217) > Ftable (3.06), and a significance value of 0.000 0.05, the findings of the F test demonstrate that service quality and customer satisfaction simultaneously affect customer loyalty at the Supermarket Brastagi Gatot Subroto Medan. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty